2015
DOI: 10.1590/1982-0216201510614
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de utilização da técnica de contagem como preditor da capacidade vital lenta em indivíduos hospitalizados

Abstract: OBJETIVO:avaliar se existe correlação entre a capacidade vital lenta e o tempo máximo de fonação, mais especificamente pela técnica de contagem numérica e se é possível a partir do tempo máximo de fonação estimar a capacidade vital lenta em indivíduos hospitalizados.MÉTODOS:trata-se de um estudo do tipo transversal, crossover e a escolha das técnicas (espirometria e técnica de contagem numérica) foram realizadas de forma randomizada (sorteio simples). A capacidade vital lenta foi mensurada por meio da espirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This systematic review aimed to verify the applicability of SBCT as a VC assessment parameter. Of the 11 selected studies, nine (82%) observed that there was a relationship between these variables through correlation and linear regression [12,13,16,[38][39][40][41][42][43]. Only two articles evaluated the accuracy of the test, one of which identified a cutoff point of 21 in the SBCT to predict low lung function (SVC < 20 ml kg −1 ) 4B -NIH quality assessment tool for cross-sectional studies Study in hospitalized patients with various diseases [8] and another estimated a count lower than 41 for a VC below 80% of predicted in patients with NMD [43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review aimed to verify the applicability of SBCT as a VC assessment parameter. Of the 11 selected studies, nine (82%) observed that there was a relationship between these variables through correlation and linear regression [12,13,16,[38][39][40][41][42][43]. Only two articles evaluated the accuracy of the test, one of which identified a cutoff point of 21 in the SBCT to predict low lung function (SVC < 20 ml kg −1 ) 4B -NIH quality assessment tool for cross-sectional studies Study in hospitalized patients with various diseases [8] and another estimated a count lower than 41 for a VC below 80% of predicted in patients with NMD [43].…”
Section: Discussionmentioning
confidence: 99%
“…The selected articles included one diagnostic accuracy study [8], one concordance study [15], seven crosssectional [12,13,16,[39][40][41][42], and two that did not inform the design [43,44]. They were conducted in five countries, Brazil [8,12,15,16,40,42], Saudi Arabia [41], Argentina [39], Germany [43] and the USA [13,44]. The age of participants was wide across studies, ranging from 12 to 59 years.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations